El emprendimiento dentro de las mallas curriculares en las facultades de administración de la ciudad de Quito. Un estudio exploratorio de la realidad académica actual - Hallo Alvear, Rodrigo Fernando (2018)
The institutions of higher education IES are governed by laws and regulations promulgated to guarantee quality professional training with relevance and articulated to the needs of transformation and social participation; This training seeks to meet a specific egress profile according to each area of knowledge, in administration is to use the administrative elements to design, model and generate processes in organizations within a changing market that meet the needs of consumers generating Shareholders and / or society. However, professionals who graduate from higher education institutions become part of the labor market in a dependency or independent relationship, the latter of which generate entrepreneurship, many of them considered "swallows" due to their short time of permanence in the market. The present research seeks to reach quantitative conclusions on the number of subjects in the curricular meshes of the public and private university administration faculties in the city of Quito, which develop students' entrepreneurship skills